2019
DOI: 10.1002/cfp2.1061
|View full text |Cite
|
Sign up to set email alerts
|

Examining the gender pay gap among financial planning professionals: A Blinder‐Oaxaca decomposition

Abstract: The financial planning industry has been identified as having one of the largest gender pay gaps. This study examines whether male and female financial planners receive equal pay for equal work. Using detailed data on the backgrounds and practices of 710 financial planners, an unadjusted pay gap of 19% was observed between male and female financial planners. Blinder‐Oaxaca decomposition analysis suggests that 91% of this pay gap can be explained by a model accounting for differences in important individual cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…51% of this gender pay gap could be explained by other factors considered in this analysis. While the explained portion of the gender pay in this study is less than explained portions in prior studies of the financial advisory industry-e.g., Tharp et al (2019) found 91% of the gender pay gap could be explained by factors considered within their model-the data within the present dataset did not include the psychological factors that were found to explain the largest portion of the gender pay gap among financial advisors. The present finding is largely consistent with the gender pay gap literature, as the gap after controlling for other factors is smaller yet still indicative of higher income for men.…”
Section: Exploratory Decomposition Analysescontrasting
confidence: 56%
See 4 more Smart Citations
“…51% of this gender pay gap could be explained by other factors considered in this analysis. While the explained portion of the gender pay in this study is less than explained portions in prior studies of the financial advisory industry-e.g., Tharp et al (2019) found 91% of the gender pay gap could be explained by factors considered within their model-the data within the present dataset did not include the psychological factors that were found to explain the largest portion of the gender pay gap among financial advisors. The present finding is largely consistent with the gender pay gap literature, as the gap after controlling for other factors is smaller yet still indicative of higher income for men.…”
Section: Exploratory Decomposition Analysescontrasting
confidence: 56%
“…Characteristics that highlight their femininity (e.g., being a mother) tend to accentuate their perceived "lack of fit" with the masculine occupation (Heilman & Okimoto, 2008;Heilman & Parks-Stamm, 2007). According to Current Population Survey (CPS) figures published by the U.S. Bureau of Labor Statistics, financial advisors have one of the largest unadjusted pay gaps of all tracked occupations (Fottrell, 2018;Kurtz, 2017Kurtz, , 2018Zulz, 2016), with female financial advisors earning 65 cents for every dollar earned by male financial advisors, 5 although this gap has been found to be smaller when adjusting for relevant advisor characteristics (Tharp, Lurtz, Mielitz, Kitces, & Ammerman, 2019). Examining how family structures like marriage and parenthood differentially affect men and women is important in this environment.…”
Section: Advisorsmentioning
confidence: 99%
See 3 more Smart Citations